2018
DOI: 10.3791/58071
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Epithelial Abrasion with Ocular Burr As a Model for Cornea Wound Healing

Abstract: The murine cornea provides an excellent model to study wound healing. The cornea is the outermost layer of the eye, and thus is the first defense to injury. In fact, the most common type of eye injury found in clinic is a corneal abrasion. Here, we utilize an ocular burr to induce an abrasion resulting in removal of the corneal epithelium in vivo on anesthetized mice. This method allows for targeted and reproducible epithelial disruption, leaving other areas intact. In addition, we describe the visualization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…S5A). Nevertheless, we confirmed a delay in our corneal abrasion model (Kalha et al, 2018a) (Fig. S5B), and analyzed the expression of several factors known to play a role during corneal wound healing (Klenkler et al, 2007;Yan et al, 2016) (Fig.…”
Section: Eda Loss Of Function Results In Impaired Lg Maturationsupporting
confidence: 63%
See 2 more Smart Citations
“…S5A). Nevertheless, we confirmed a delay in our corneal abrasion model (Kalha et al, 2018a) (Fig. S5B), and analyzed the expression of several factors known to play a role during corneal wound healing (Klenkler et al, 2007;Yan et al, 2016) (Fig.…”
Section: Eda Loss Of Function Results In Impaired Lg Maturationsupporting
confidence: 63%
“…Cornea injuries were performed on anesthetized 13 wo animals as previously described (Kalha et al, 2018a). In brief, an ocular burr (Algerbrush II, BR2-5 0,5 mm, Alger company) was used to remove an area of the central cornea epithelium, avoiding peripheral and limbal regions.…”
Section: Cornea Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…In case of a deeply embedded foreign object, corneal irregularities might form, resulting in significant visual disruption. Previously, we showed that murine corneal wound closure was based on cell rearrangements (Kalha et a.l, 2018a), and tear composition was quickly modified after corneal insult (Kuony et al, 2019). These changes in corneal microenvironment, undoubtly supporting corneal healing, were crucial for proper wound closure, by bringing a new mix of factors through the tears when needed, for instance to support corneal wound healing after insult.…”
Section: Introductionmentioning
confidence: 99%
“…An elegant study demonstrated that epithelial renewal is similar in zebrafish and mammalian cornea (Pan et al, 2013). Indeed, both forms of epithelial renewal were found in mouse (Kalha et al, 2018a) and zebrafish (Pan et al, 2013). A local one, based on progenitor cells, and a global one, based on stem cells located at corneal periphery in a structure called limbus.…”
Section: Introductionmentioning
confidence: 99%